Trabectedin modulates the senescence-associated secretory phenotype and promotes cell death in senescent tumor cells by targeting NF-κB - Camorani, Simona (Oncotarget, 2018)
Therapy-induced senescence is a major cellular response to chemotherapy in solid tumors. Senescent tumor cells acquire a secretory phenotype, or SASP, and produce pro-inflammatory factors, whose expression is largely under NF-κB transcriptional control. Secreted factors play a positive role in driving antitumor immunity, but also exert negative influences on the microenvironment, and promote tumor growth and metastasis. Moreover, subsets of cancer cells can escape the senescence arrest, driving tumor recurrence after treatments. Hence, removal the senescent tumor cells, or reprogramming of the senescent secretome, have become attractive therapeutic options. The marine drug trabectedin was shown to inhibit the production of pro-inflammatory mediators by tumor-infiltrating immune cells and by myxoid liposarcoma cells. Here, we demonstrate that trabectedin inhibits the SASP, thus limiting the pro-tumoral activities of senescent tumor cells in vitro. We show that trabectedin modulates NF-κB transcriptional activity in senescent tumor cells. This results in disruption of the balance between antiapoptotic and proapoptotic signals, and sensitization of cells to Fas-mediated apoptosis. Further, we found that trabectedin inhibits escape from therapy-induced senescence, at concentrations that do not affect the viability of bulk tumor population. Overall, our data demonstrate that trabectedin has the potential to inhibit multiple detrimental effects of therapy-induced senescence.